Respirators for Pesticide Applications - Frederick M. Fishel (EDIS, 2010)
Revised! PI-77, a 6-page illustrated fact sheet by Frederick M. Fishel, provides guidance for selecting an appropriate respirator and using it properly. Includes additional sources of information. Published by the UF Department of Agronomy, May 2010.